Influence of a minimum wage on incomes of population and the amount of remuneration in free market economy - Szczepanik, Maciej (Publishing House of the Wrocław University of Economics, 2009)
The purpose of this paper is to determine an influence of a top-down established minimum wage on real incomes of households and on the level of real remuneration in free market economy. “Level of remuneration” is understood as an average monthly salary on the national scale. The subject of the analysis will be mainly a change in general level of remuneration in national economy, not the change of individual remuneration. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 432-441